2008
DOI: 10.1016/j.ijid.2008.05.980
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Nosocomial Infections at a Saudi Arabian Military Hospital for a One-Year Period

Abstract: The objectives of the current study are to define how many and what kind of nosocomial infections are occurring, what are the causative microbes and what kind of drugs can be used in treatment of infection at Al-Hada Armed Forces Hospital, Taif, Saudi Arabia during the year 2004. A prospective study was implemented for all cases admitted at Al-Hada Armed Forces Hospital during the period 1st January, 2004 till 31st December, 2004 and which developed infection. Determination of nosocomial infections was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
5
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 24 publications
(36 reference statements)
3
20
5
2
Order By: Relevance
“…The association between sex prevalence of Proteus spp showed that the rate among males and (23.6%) female agreed with Saudi Arabia reported by [24] (75.0%) males and (25.0%) females. The prevalence of ESBL producing Proteus spp was 13.1% lower than reported from India 24% [29], 31.1% [30] and Ghana 72.9% [28] and higher than France 6.9% reported by De Champs et al, [31].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The association between sex prevalence of Proteus spp showed that the rate among males and (23.6%) female agreed with Saudi Arabia reported by [24] (75.0%) males and (25.0%) females. The prevalence of ESBL producing Proteus spp was 13.1% lower than reported from India 24% [29], 31.1% [30] and Ghana 72.9% [28] and higher than France 6.9% reported by De Champs et al, [31].…”
Section: Discussionsupporting
confidence: 87%
“…This study, prevalence of ESBLs-producing Proteus spp was found to be high 5.1% compared to the prevalence recorded from Saudi Arabia (3.0%) [24] (2.9%) [25] and India (3.04%) [26] and (1.12%) [27] but this result was low compared to those reported from Ghana (8.4%) [28] with the 68.4%, 31.6% rate among the Proteus spp (P. mirabilis and P. vulgaris) respectively which similar to Indian studies (62.2%) P. mirabilis & (32.5%) P. vulgaris reported by Syntem et al, [29] and Ghana (61.5%) P. mirabilis & (30.5%) P. vulgaris [28].…”
Section: Discussioncontrasting
confidence: 67%
“…[28] Ampicillin was the least active with a resistance rate of 88.6%. The previous rate is relatively higher than the rate which reported by a recent performed in Taif [29] in which 73.4% of the isolates were resistant to ampicillin. This suggests an increase of 15.2% in the incidence of resistance to ampicillin over the last eleven years.…”
Section: Discussioncontrasting
confidence: 57%
“…Garibaldi et al (1991) acompanharam ISC em pacientes humanos durante quatro anos, identificando em cultura de colheita intra-operatória os microrganismos Staphylococcus (78%) e Escherichia (11%). Já Abdel-Fattah (2005) isolou Pseudomonas, Klebsiella, Citrobacter e Enterobacter, identificando maior taxa de bactérias Gram-negativas em comparação às Gram-positivas, concordando com os dados encontrados no hospital humano. Já Ishii et al (2011) ao realizarem estudo em hospital veterinário, detectaram maiores taxas de bactérias Gram-positivas em comparação às Gram-negativas, concordando com os dados encontrados no hospital veterinário.…”
Section: Discussionunclassified